Sosialisasi dan Skrining Sindrom Metabolik melalui Pengukuran IMT, Tekanan Darah, serta Pemeriksaan Glukosa Darah pada Orang Dewasa di Masa Pandemi Covid-19 - Wikandari, Ririh Jatmi; Purlinda, Devi Etivia (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Metabolic syndrome is caused by a poor lifestyle, excessive food consumption, lack of physical activity. Someone with metabolic syndrome will be more susceptible to Covid-19. This community service activity aims to provide knowledge about metabolic syndrome as well as measurement of Body Mass Index (BMI), measurement of blood pressure and checking blood glucose levels. The method of carrying out activities is in the form of outreach related to metabolic syndrome and screening for metabolic syndrome through BMI measurements, measuring blood pressure using a digital tensimeter and checking blood glucose levels using the Point of Care method. The activity was carried out in Bangetayu Kulon RT 07 RW 01 Semarang City on May 13-15 2022. The target audience is adults aged 20-65 years with a total of 56 people. From the results of the examination, it was found that 87.5% of respondents had hypertension, 12.5% of respondents had diabetes mellitus and 73.2% of respondents were obese. Community service activities provide an overview of public health about metabolic disorders so that it is hoped that after this activity the community routinely conducts health checks to prevent metabolic syndrome.